Modeling, optimization, and experimental evaluation of remotely pumped double-pass EDFA - Hossain, Nadir; Naji, A. W.; Mishra, V.; Abbou, F. M.; Al-Mansoori, Mohammed Hayder; Mahdi, M. A.; Faidz, A. R. (Wiley Periodicals, 2007)
A simple rate equation model of double pass (DP) Erbium-doped fiber amplifier (EDFA) is developed based on the Giles and Desurvire (1991) model of single pass (SP) EDFA. The mathematical equations to calculate stimulated absorption and emission rate between levels 1 and 2 of SP EDFA are modified by integrating the reflected backward propagating signal of DP EDFA. Reflection loss of signal by the reflector is included with the backward propagating signal of DP EDFA. The design parameters of DP EDFA are optimized using numerical simulation of the developed DP EDFA rate equation model to design remotely pumped optimized DP EDFA. Robustness and stability of the developed DP EDFA rate equation model are shown by analyzing the numerical results and output shapes, using various design parameters of DP EDFA. Finally, the developed DP EDFA rate equation model is validated with the help of experimental results. (C) 2007 Wiley Periodicals, Inc.